Founder of the Ecological Movement in Costa Rica: Ricardo Quesada López - Calleja (Biocenosis, 2022)
Ricardo Quesada López-Calleja was born in Barrio Amón, San José, Costa Rica on August 31, 1929. He was the youngest son of Víctor Quesada Carvajal and Hortensia López-Calleja Mora.  Educated both in private and public schools, he graduated as a lawyer from the University of Costa Rica.  As a teenager, he worked in the Castro & Quesada Warehouse with his father. It is said that it was Quesada López-Calleja who started and transformed foreign trade in Costa Rica by establishing business relationships with different Eastern European countries, where he was appointed Ambassador.  In the 70’s, he taught in the Escuela Normal Superior, and in the School of Political Science at the University of Costa Rica. Quesada published different iconographies from leaders of the world, some other works related to archeological artifacts in the National Museum, and his masterpiece Costa Rica. La Frontera Sur de Mesoamérica.  Founder of the environmental movement in Costa Rica, he created along with a group of students, professors, and friends, the National Patrimony Defense Committee on April 24, 1970. Later on, he participated in important environmental efforts seeking to protect the country’s archaeological and natural patrimony, to introduce an environmental amendment in the Constitution of Costa Rica (Art. 50), and to enact the Environmental Law. Ricardo Quesada López-Calleja died on January 31, 1994, and, as the founder of the environmental movement, this was his legacy to the people of Costa Rica.
Keywords: international trade; iconography; national patrimony; environmental movement; National Patrimony Defense Comittee; environmental legislation